Pemberdayaan Masyarakat melalui Pelatihan Partisipatif Olahan Pisang Khas Lampung - Sariningsih, Eka; Kurniawati, Septi; Wulandari, Siti Ayu; Sakinah, Albayati Spink Putri; Fadhilah, Annisa Nur (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: The training program on banana processing conducted in Sumber Agung Village, Kemiling District, Bandar Lampung City, aims to enhance the added value of local agricultural commodities, particularly bananas, which are the village’s leading produce. Through this activity, the community is empowered to process bananas into various high–economic–value products such as banana pies, banana cakes, banana chips, and banana jam. With product diversification, it is expected that bananas will no longer be sold merely in their raw form at low prices but transformed into distinctive local souvenirs that can compete in both local and regional markets. Methodology/approach: This study employs a participatory approach that directly involves the community in all stages of the training process—from planning and implementation to evaluation. Data were collected through in-depth interviews with participants, observations of production processes, and surveys of banana plantations and yields. Results/findings: The results indicate that the training successfully improved community skills, created new business opportunities, and increased household income among participants. Conclusions: The program effectively enhanced community empowerment through skill development and value-added production of local commodities, showing significant potential for economic improvement. Limitations: Several challenges remain, including limited business capital, difficulties in obtaining additional raw materials, and a lack of marketing skills. Contributions: This program has strong potential to serve as a model for local economic empowerment that can be replicated in other villages with similar agricultural commodities.